2019
DOI: 10.1111/trf.15324
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the risk, cost‐effectiveness, and perceived benefits of anti‐parvovirus B19 tested blood products

Abstract: BACKGROUND: Parvovirus B19 (B19V) can cause severe anemia, hydrops foetalis, and even death in vulnerable patients. To prevent transfusion-transmitted B19V infection of at-risk patients, B19V antibody screening of blood donors was implemented. The costeffectiveness of this intervention is unclear, as the likelihood of transmission through blood and subsequent complications for recipients are unknown. This study estimates the cost-effectiveness of anti-B19V donor screening in the Netherlands.ABBREVIATIONS: Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Eight studies reported a selection method that used convenience sampling in which experts were selected due to their proximity to the study team. 39,45,46,49,51,59,68,69 Of the remaining studies, 4 used publication records, 13,14,64,66 2 used prescribing records to identify clinicians who have used the medications being evaluated, 67,71 2 consulted external advisors, 52,58 and the rest used snowball sampling, 64,70 trial involvement, 12 all certified obstetricians/gynecologists in the country of study with years of experience, 55 or international reputation. 61 The average number of experts recruited per EE was 11, with a range of 1 to 30.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies reported a selection method that used convenience sampling in which experts were selected due to their proximity to the study team. 39,45,46,49,51,59,68,69 Of the remaining studies, 4 used publication records, 13,14,64,66 2 used prescribing records to identify clinicians who have used the medications being evaluated, 67,71 2 consulted external advisors, 52,58 and the rest used snowball sampling, 64,70 trial involvement, 12 all certified obstetricians/gynecologists in the country of study with years of experience, 55 or international reputation. 61 The average number of experts recruited per EE was 11, with a range of 1 to 30.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent methods were Delphi or modified Delphi process ( n = 10), 13,36,37,41,42,47,55,58,61,66 while 2 used the SHELF method 63,64 ; both methods rely on multiple rounds of discussion to build consensus among experts. Elicitations were frequently done virtually or over the phone ( n = 13) 14,36,41,46,48,50,53,55,57,66,67,70,71 while only 5 specified that the elicitation was conducted in person. 38,39,48,51,60 Web- or spreadsheet-based elicitation tools were used to facilitate data collection in 9 elicitations.…”
Section: Resultsmentioning
confidence: 99%
“…Their results revealed a mean of 18.2 infected blood products per year (0.004% of erythrocyte concentrates and 0.03% of thrombocyte concentrate). They concluded that 5.33 infections could be prevented by that screening annually 45 . However, it needs to be considered that these numbers are difficult to compare between different countries due to regional and also seasonal outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that 5.33 infections could be prevented by that screening annually. 45 However, it needs to be considered that these numbers are difficult to compare between different countries due to regional and also seasonal outbreaks. 46 In Germany, between 1997 and 2017, there has been no single case of a transfusion-associated B19V infection reported to the Paul-Ehrlich Institute, supporting the absence of a general recommendation for a blood product screening of B19V in Germany.…”
Section: Discussionmentioning
confidence: 99%